Evidence-Based Practice in Clinical Hypnosis. - Milling, Leonard (American Psychological Association, 2023)
This book details the scientific evidence for and the clinical practice of hypnosis for a range of problems and symptoms, including anxiety, depression, acute pain, chronic pain, and other behavioral problems.